From Global Justice to Occupy and Podemos: Mapping Three Stages of Contemporary Activism - Peter N. Funke; Todd Wolfson (tripleC: Communication, Capitalism & Critique)
Surveying the varied contributions to this special issue, this article examines the relationships, points of inspirations and contradictory dynamics that characterize the current epoch of social movement politics and global protest. The authors argue that with the progression of neoliberal capitalism and the explosion of new technologies, a shared logic of social movement politics has emerged. This logic spans from the Zapatistas and the Global Justice Movement to the uprisings in North Africa and the Middle East, the Occupy struggles and the most recent wave characterized by Podemos. While each of these waves of contention has a particular character, together they make up a broader epoch of struggle that thrives on multiplicity, emphasized radical participatory democracy, the innovative use of media and the heterogeneity of political struggle.